KEANEKARAGAMAN JENIS BURUNG PADA KAWASAN HUTAN LINDUNG KPH DAMPELAS TINOMBO DI DESA SIBUALONG KEC. BALAESANG KAB. DONGGALA - Rudini, Rudini; Labiro, Elhayat; Ihsan, Moh. (Jurnal Warta Rimba, 2016)
There are 1,539 bird species found in Indonesia, 381 of those species are endemic to Indonesia and 250 species endemic spread around Wallacea region.Wallacea region includes Sulawesi Island and nearby islands, they are Banggai Island, Sula Island, Nusa Tenggara Island, and Maluku Island.Birds are fauna which can be found from the lowlands to highlands, both in natural area or any other areas.The study about Birds’ species was conducted on March until May 2015 in order to determine composition, level of presence, diversity index, evenness index, and dominance of bird species in Protected Forest of Forest Management Unit Dampleas Tinombo, Sibualong Village, Balaesang Sub district, Donggala District. The method used was line transect method which function to record bird species. This method was applied to the research object along predetermined transects. Length line of transect is 500 meters.There are 4 line transects.The study result shows that there are 29 bird species represent 20 families with the total number of all species are 98 birds. There are several bird species were found from all observation center with level of presence is 100% type of forest habitat which is known well as brown-throated sunbird (Antrepthesmalacensis).Diversity index of bird species according to the type of forest habitat is about H '= 3.060394, whereas in open habitat is H' = 2.589035.Based on t test, for the diversity index discovered that there is no difference between the types of forest habitat and open habitat in the observation center, then it is concluded that H0 is accepted.Key words: diversity species, birds, protected forest